First Grader’s Attention Span During In-Class Activity - Asprilia, Mutiara Tioni; Qodariah, Laila; Purba, Fredrick Dermawan (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2020)
Learning is closely related to one's ability to give focus and attention to instructional activities. The ability to maintain attention for a period of time is especially critical between 6 and 7 years. At this age, children's attentional abilities are not fully developed. This study aimed to gain knowledge of actual behavior related to the attention span of first graders in elementary school during classroom activities. The data was obtained by observing one grade 1 elementary school in its natural setting with the time sampling method. Observations are based on the 'on-task and 'off-task behavior shown by the students. What found that the longest time elementary school grade 1 students were able to show 'on-task behavior indicating their attention span was 7 minutes. These results indicate a gap with the expected attention span of grade 1 elementary school children, which is about 18 minutes.